Analisa Kinerja Lalu Lintas Simpang Tiga Tidak Bersinyal Studi Kasus Jalan KH Ismail Malik-Jalan Raden Syahbudin Kota Jambi - Hendra Hasudungan Silaban; Amsori M Das; Ari Setiawan (Universitas Batanghari Jambi, 2023)
This study aims to determine traffic performance at intersections using the 2014 PKJI guidelines, so as to determine the capacity value at the intersection and the Degree of Saturation value to continue research by providing solutions to the problems that occur. This research method uses PKJI 2014 guidelines to obtain vehicle volume and road width values at the research location for further analysis. it is known that the peak hour with a total volume value (Q) of 2010.8 cur/hour, a capacity value (C) of 2203 cur/hour, degree of saturation (Dj) = 0.91, delay (T) = 15.96 sec/ cur and the value of the Queue Opportunity (PA) (65.53% - 33.22%). Judging from the results of the degree of saturation, the location of this study did not meet the requirements in the 2014 PKJI, where if the value of the degree of saturation was ≥ 0.85, a design change was required. The service level in this study was C (15.1 – 25.0) in the medium category. After re-calculation by redesigning the width of the minor road approach, moving the market, installing prohibited parking signs along the intersection approach and recommending the placement of bus routes at this research location, assuming the bus passengers are full. Then the resulting value of Capacity (C) is 2319.7 cur/hour, with a Degree of Saturation (Dj) value of 0.84. Where the Dj value meets the requirements of the Indonesian Road Capacity Guidelines (PKJI 2014).